Комплексний розвиток регіонів як основа якості життя населення - Нехайчук, Д.В.; Нехайчук, Ю.С. (Культура народов Причерноморья, 2014)
У науковій статті розглянуто поняття комплексного розвитку регіонів та надано
авторське тлумачення дефініції. Виокремлено збалансованість розвитку території як одного з аспектів
в низці проблеми досягнення комплексності розвитку району. Виділено основні складові процесу
комплексного розвитку регіону. Зроблено висновки щодо посилення тенденцій концентрації та
централізації продуктивних сил, підтримання гнучкою пропорційності всіх елементів господарювання. В научной статье рассмотрено понятие комплексного развития регионов и представлено
авторское толкование дефиниции. Выделена сбалансированность развития территории как один из
аспектов в ряде проблем достижения комплексности развития района. Выделены основные
составляющие процесса комплексного развития региона. Сделаны выводы об усилении тенденций
концентрации и централизации производительных сил, поддержании гибкой пропорциональности всех
элементов хозяйствования. The author interpretation the concept of integrated development of regions and presents of the
definition in the scientific article. The author identifies a balanced development of the area as one of the aspects
of a number of issues to achieve integrated development of the district.
The author argues that a comprehensive development should covercover all areas of human life: material
production and non-production sphere, infrastructure, resettlement and zaynyatost population, the use of natural
resources. Highlights the main components of the integrated development of the region.
The researcher argues that economic efficiency is achieved through the development of specialized production
and inter-sectoral cooperation, reproductive balance, development of regional infrastructure substitutability and
complementarity of different types of resources, as well as centralized management and other factors. Different
regions of the labor availability, material and financial resources, production and consumption imbalances,
supply and demand and other factors affect the duration of the market economy in different regions, the pace
and ways of forming regional markets.
There are conclusions are drawn about the increasing trend of concentration and centralization of the
productive forces, maintaining flexible proportionality of all elements of management.